Forage Availability and the Effects of Dry Season Patch Burning on Diet and Habitat Selection by the Common Eland in Eland Sanctuary Park, Zimbabwe (Journal of Wildlife and Conservation, 2024)
Common elands are also kept in small fenced areas where they utilise different habitats in search of forage when scarce. Ecologists need to understand forage availability and determine how dry season patch burning can influence diet selection of the common elands in protected areas and this prompted the study in the Eland Sanctuary Park. Two sites were selected: i.e. burnt and unburnt. The burning exercise was done on the 16th of June, 2023 and the area was left for two weeks for regrowth. Forty random sample plots were set on the 1st of July, 2023, consisting of twenty-four in unburnt and sixteen in burnt site each of size 25m x 25m. Data collection was done from the 1st to 10th of July, 2023, recording number of plant species utilised and eland spoors in each plot. Plant species selectivity was determined using preference ratios and frequencies of acceptance which was calculated at species level. Mann-Whitney U-test was used to determine the significant differences in common eland spoor density between burnt and unburnt areas at p = 0.05 after the Kolmogorov-Smirnov normality test at p = 0.005 (N =24, P= 0.070). Results showed that Macaranga capensis, Pinus patula, and Sclerocarya birrea had a high preference ratio in the unburnt area, while, Laodetia simplex, Cymbopogon plurinodis, and Themeda triandra had a high acceptance rate after burning. However, there was no strong correlation between spoor abundance and number of plants utilised in both burnt and unburnt areas. Ecologists should acknowledge dry season patch burning at intervals to facilitate regrowth and retain forage palatability for the common eland.